If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-3b + -2) = -15 Reorder the terms: 3(-2 + -3b) = -15 (-2 * 3 + -3b * 3) = -15 (-6 + -9b) = -15 Solving -6 + -9b = -15 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -9b = -15 + 6 Combine like terms: -6 + 6 = 0 0 + -9b = -15 + 6 -9b = -15 + 6 Combine like terms: -15 + 6 = -9 -9b = -9 Divide each side by '-9'. b = 1 Simplifying b = 1
| -3y-14=2y+11 | | h(x)=3x^2+15x+50 | | x^2+6x-4=36 | | 4x-2=8x+5 | | 9x-10=197 | | 1x-20y=2 | | 8-5x=5+8x | | D=Nrk | | 6z^2-11z+4=0 | | x^2+4x-154.5=0 | | 24x^2-68x+48= | | 5/6*4/15 | | 2400=600-40x | | 3y-4+y+40=5y+40-3y | | .04x+8.1=6.7 | | -3(9+A)=-72 | | (5x+30)+(x+90)=180 | | 10x(2x-5)(x-1)= | | x/9=80/100 | | 36x^2+171x+189= | | (-6)-(-5)+(-4)= | | y=30*3/4 | | 29=52-x | | y=30*2/3 | | 44=x-21 | | .04x+4.3=2.9 | | 41=x+18 | | -6(M-8)=8(m+6) | | y=30*1/2 | | 9x^2-30x+16= | | y=30x1/2 | | -9/3-(-12) |